The Philosophy of Progressivism as the Basis for Instilling the Pancasila Student Profile in Elementary Education - Serita Andana; Danu Hendroto (Cattleya Darmaya Fortuna, 2025)
Basic education is an important foundation in shaping the character and personality of students. In the context of the Merdeka Belajar curriculum, the Pancasila Student Profile is the direction of educational goals that emphasize the development of the values ​​of diversity, mutual cooperation, independence, critical thinking, creativity, and faith and devotion to God Almighty. The philosophy of progressivism, with its emphasis on direct experience, active learning, and the development of individual potential, is in line with the spirit of the formation of the Pancasila Student Profile. This article aims to examine the role of the philosophy of progressivism as a basis for instilling the values ​​of the Pancasila Student Profile in elementary schools. Through a qualitative approach and literature study, it was found that the application of the principles of progressivism in learning is able to create a participatory, democratic, and contextual educational environment, which supports the realization of students who are in accordance with the values ​​of Pancasila. Thus, progressivism is not only relevant, but also strategic in supporting the transformation of education in Indonesia.